Modification of Bacillus sp. IMV B-7883 Elastase Activity by the Hetero-Metallic Carboxylatogermanates/Stannates - Gudzenko, O.V.; Varbanets, L.D.; Seifullina, I.I.; Martsynko, O.E.; Buchko, O.V.; Afanasenko, E.V.; Chebanenko, О.A.; Гудзенко, O.В.; Варбанець, Л.Д.; Сейфулліна, І.І.; Марцинко, О.Є.; Бучко, О.В.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
In recent years, some researchers have found that although many Gram-negative and Gram-positive bacteria secrete elastase, the bacterial forms of elastase have either a low activity or harmful effects. Therefore, further research is needed in isolating and screening microorganisms that produce a high level of elastase activity. Previously we selected strain Bacillus sp. IMV B-7883, which exhibits fairly high elastase activity. To increase its activity, we chose one of the well-known approaches, in particular, the use of a number of coordination compounds capable to influence elastase activity. In this regard, the purpose of this work was to study the effect of such coordination compounds as hetero-metallic carboxylatogermanates/stannates on the elastase activity of Bacillus sp. IMV B-7883. Methods. The object of the investigation was the strain of Bacillus sp., deposited in the Ukrainian Collection of Microorganisms under the number IMV B-7883, isolated from soil. The culture was grown under conditions of submerged cultivation at 28 °С, with a mixing speed of the nutrient medium of 244 rpm for three to six days (72–144 hours). We used an enzyme purified from the supernatant of the culture liquid by precipitation with 90% ammonium sulfate, with further fractionation on neutral and charged carriers. Elastase activity was determined colorimetrically by the intensity of the color of the solution upon enzymatic hydrolysis of elastin stained with Congo red. As modifiers of enzyme activity, hetero-metallic carboxylatogermanates/stannates were used. Results. Of the 15 studied in this work coordination compounds presented by hetero-metallic carboxylatogermanates/stannates, only 1 [Ba(H2O)6][Ge2(OH)2(C6H8O7)2]·nH2O, n=2 and 3 [Ni (H2O)6][Ge2(OH)2(C6H8O7)2]·nH2O, n=4, depending on the concentration used and incubation time, increase the elastase activity by only 3–5%. All other compounds have an inhibitory effect. Conclusions. Obtained data on the inhibitory effect of hetero-metallic carboxylatogermanates/stannates on the elastase activity of Bacillus sp. IMV B-7883 provide new information which may help in solving the issue of the mechanism of interaction between enzymes and complex chemical molecules.